Early Diagnosis of Herpes Simplex Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs, 2003)
Records of 38 patients, 23 boys and 15 girls (ages 3 months to 16 years [42% ages 3-12 months]), seen between 1990 and 1997 with proven herpes simplex encephalitis (HSE), were reviewed retrospectively to determine the diagnostic reliability of polymerase chain reaction (PCR) results, in a study at the Neuropediatric Service, Hopital Saint Vincent de Paul, Paris, France.